Carbon isotope composition as a tool for quality control of herbs, spices and medicinal plants - Marchese, Jose Abramo [UNESP]; Ming, Lin Chau [UNESP]; Ducatti, Carlos [UNESP]; Silva, Evandro Tadeu da [UNESP]; Khan, I. A.; Smillie, T. J.; Craker, L. E.; Gardner, Z. E. (Int Soc Horticultural Science, 2006)
Isotope screening is a simple and cheap test for determining the photosynthetic pathway used by plants. The scope of this work was to classify the photosynthetic type of Melissa officinalis L. and Cymbopogon citratus [DC.] Stapf. through studies of the carbon isotope composition (delta C-13), and we are proposing the use of carbon isotope composition results as a tool to control the quality of medicinal plants. For studies of delta C-13 (delta C-13% = [R (sample)/R (standard) - 1] x 10(-3)), dried, powdered leaves were analyzed in a mass spectrometer coupled with an elemental analyzer for determining the ratio R (R = (CO2)-C-13/(CO2)-C-12). As results, M. officinalis presented a C-3 photosynthetic type, and C citratus presented a C-4 photosynthetic type. The carbon isotope composition from this study can be used as quality control of M. officinalis adulterants.
Keywords: botanicals; C-3 and C-4 plants; isotope discrimination; photosynthesis